Adverse events in a large‐scale VMMC programme in Tanzania: findings from a case series analysis. Issue 7 (31st July 2019) - Hellar, Augustino; Plotkin, Marya; Lija, Gissenge; Mwanamsangu, Amasha; Mkungume, Saidi; Christensen, Alice; Mushi, Jeremiah; Machaku, Michael; Maokola, Thomas; Mlanga, Eric; Curran, Kelly
Abstract: Introduction: Adverse events (AEs) rates in voluntary medical male circumcision (VMMC) are critical measures of service quality and safety. While these indicators are key, monitoring AEs in large‐scale VMMC programmes is not without challenges. This study presents findings on AEs that occurred in eight years of providing VMMC services in three regions of Tanzania, to provide discussion both on these events and the structural issues around maintaining safety and quality in scaled‐up VMMC services. Methods: We look at trends over time, demographic characteristics, model of VMMC and type and timing of AEs for 1307 males who experienced AEs among all males circumcised in Tabora, Njombe and Iringa regions from 2009 to 2017. We analysed deidentified client data from a VMMC programme database and performed multivariable logistic regression with district clustering to determine factors associated with intraoperative and postoperative AEs among VMMC clients. Results and discussion: Among 741, 146 VMMC clients, 0.18% (1307/741, 146) experienced a moderate or severe AE. The intraoperative AE rate was 2.02 per 100, 000 clients, and postoperative rate was 2.29 per 1000 return clients. Multivariable logistic regression showed that older age (20 to 29 years) was significantly associated with intraoperative AEs (aOR: 3.51, 95% CI: 1.17 to 10.6). There was no statistical significant difference in AE rates by surgical method. Mobile VMMC service delivery was associated with the lowest risk of experiencing postoperative AEs (aOR:0.64, 95% CI: 0.42 to 0.98). AE rates peaked in the first one to three  years of the programme and then steadily declined. Conclusions: In a programme with robust AE monitoring methodologies, AE rates reported in these three regions were very low and declined over time. While these findings support the safety of VMMC services, challenges in reporting of AEs in a large‐scale VMMC programme are acknowledged. International and national standards of AE reporting in VMMC programmes are clear. As VMMC programmes transition to national ownership, challenges, strengths and learning from AE reporting systems are needed to support safety and quality of services.